2021
DOI: 10.1109/access.2021.3052025
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Mapping of Open Data Studies: Classification and Trends From a Technological Perspective

Abstract: The objective of this paper is to classify and analyse all research on open data performed in the scientific community from a technological viewpoint, providing a detailed exploration based on six key facets: publication venue, impact, subject, domain, life-cycle phases and type of research. This paper therefore provides a consolidated overview of the open data arena that allows readers to identify well-established topics, trends, and open research issues. Additionally, we provide an extensive qualitative disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…While IoT and Smart city are becoming more active topics from year to year, the study in question does not strongly support this fact, as the most "fruitful" year for both topics, sensor-and real-time data, was 2018, with a slight decline in their popularity in the scientific literature in the following years. However, despite the fact that the number of studies on both topics was the highest in 2018, the trend is positive and will increase in the coming years in all digital libraries inspected, with the exception of ACM Digital Library (also in line with [31]). It can therefore be concluded that, although many studies emphasize the significance of the concepts under consideration, real-time data and sensor-generated data, in particular, are more complementary materials that are rarely central to the study, despite their high importance and economic and innovative potential.…”
Section: Science Directmentioning
confidence: 99%
See 2 more Smart Citations
“…While IoT and Smart city are becoming more active topics from year to year, the study in question does not strongly support this fact, as the most "fruitful" year for both topics, sensor-and real-time data, was 2018, with a slight decline in their popularity in the scientific literature in the following years. However, despite the fact that the number of studies on both topics was the highest in 2018, the trend is positive and will increase in the coming years in all digital libraries inspected, with the exception of ACM Digital Library (also in line with [31]). It can therefore be concluded that, although many studies emphasize the significance of the concepts under consideration, real-time data and sensor-generated data, in particular, are more complementary materials that are rarely central to the study, despite their high importance and economic and innovative potential.…”
Section: Science Directmentioning
confidence: 99%
“…Another expressive solution demonstrating the potential of open (government) data moving toward Smart Society is the WeLive project [ 31 ], whose objective is to transform the current e-government approach by facilitating a more open model of design, production and delivery of public services, based on the collaboration among different stakeholders, i.e., citizens, public administrations, private companies and research institutes. The use of such concepts as open innovation, open data and open services paradigms allowed the authors to develop the framework, enabling the co-creation of urban apps.…”
Section: Background: Society 50 and Industry 40 In The Context Of Open Government Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The questions about open data is relevant for several domains and topics as seen in a recent systematic mapping study [8]. Even if the most common domain is "infomediaries", i.e.…”
Section: Open Source and Open Datamentioning
confidence: 99%
“…In OSS development, there are accepted ways of sharing results in communities [9], and the term "open data" [8] denotes a trend in which for example public organizations provide data to other organizations. In this paper, we analyse to what extent the view on OSS and open data carry across to data for open data-driven tuning of software development tools.…”
Section: Introductionmentioning
confidence: 99%